Proximalization of Frozen Elephant Trunk Procedure: Zone 0 or 1 versus Zone 2 or 3 Arch Repair - Lee, Kwok Fai Lucius; Bhatia, Inderjeet; Chan, Tai Leung Daniel; Au, Wing Kuk Timmy; Ho, Ka Lai Cally (The Thoracic and Cardiovascular Surgeon, 2022)
Background Total arch replacement with the frozen elephant trunk (FET) procedure has changed the landscape of therapy for aortic arch diseases. The optimal landing zone for a FET is controversial. We sought to share our early and midterm results of the FET procedure as well as compare the clinical outcomes of proximal and distal FET anastomosis.Methods A total of 100 patients who underwent total arch replacement using the FET technique were identified between November 2014 and August 2021. According to the FET anastomosis over the aortic arch, patients were classified into two groups (zone 0/1 vs. zone 2/3). In-hospital mortality, complications, and midterm outcomes were assessed based on patient characteristics.Results The overall in-hospital mortality was 8%. Major complications occurred in 32% of patients, including spinal cord injury (5%), stroke (7%), and acute kidney injury requiring dialysis (7%). Zone 2/3 FET (odds ratio: 6.491, 95% confidence interval: 1.930–21.835, p = 0.003) was an independent predictor of the composite endpoint of major complications. The rate of complete false lumen thrombosis was comparable (64.3% vs. 71.4%, p = 0.567). All patients, patients with zone 0/1 FET, and patients with zone 2/3 FET had 3-year freedom from aorta-related events of 73.0, 70.2, and 75.0%, respectively. There were no significant differences (log-rank test, p = 0.500).Conclusion Compared with zone 2/3, proximalization of FET using zone 0/1 for anastomosis was associated with better early outcomes and comparable rates of midterm aorta-related events. To substantiate its use, more research on this approach is required.
Keywords: aorta/aortic; aneurysm; surgery; complications; cardiac